Effects of PSD2 on security architecture of mobile banking : a review of literature - Kaipainen, Lauri (2017)
This thesis aims to find out the changes that the Payment Service Directive (PSD2) will bring to the security architecture of mobile banking. PSD2 will create a situation where security mechanisms are separated from the actual banking application. Payment service providers must provide their Application Programming Interface for third party developers to give them access to authentication of payment transactions. PSD2 requires payments service providers to offer strong customer authentication with separate authentication mechanism from the banking application. This thesis found that academic literature about the security architecture of mobile banking does not provide a model where a separate authentication mechanism should communicate separately from the mobile banking application. Academic research could however, provide solution to use the Public Key Infrastructure of a certificateless asymmetric encryption to achieve demand of PSD2 to offer strong encryption and means to check the integrity of data and make transactions non-reputable. The research in this thesis was conducted as a systematic literature review, which found 22 academic publications about the security architecture. The comparison between the demands of PSD2 with the academic literature was done by listing security demands and responsibilities of PSD2 and comparing them with themes found from the research material.